DERMINATION OF CUSTOMER SATISFACTION AND LOYALTY: SERVICE QUALITY AND TRUST (LITERATURE REVIEW MARKETING MANAGEMENT): DERMINASI KEPUASAN DAN LOYALITAS PELANGGAN: KUALITAS PELAYANAN DAN KEPERCAYAAN (LITERATURE REVIEW MANAJEMEN PEMASARAN) - Lafau, Ertina; Lombu, Destriani; Hiya, Nirmadarningsih (UPMI Proceeding Series, 2023)
The development of the banking world in Indonesia is very rapid and modern, in both aspects variety of banking products as well as the quality and technology they have. The competition Competitiveness spurs companies to develop new innovations according to developments period with the aim of attracting consumer interest in using each product and make him a regular customer. This article reviews the factors that influence Satisfaction and Customer Loyalty, namely: Service Quality and Trust. A literature study Marketing Management. The method for writing this scientific article is a qualitative method and literature study or library research. The purpose of writing a literature review article This marketing management is to develop hypotheses that can be used for further research. The results of this literature review article are 1) Service quality influence on customer satisfaction. 2) Trust influences satisfaction customer. 3) Quality of service influences customer loyalty. 4) Trust influence on customer loyalty. 5) Customer satisfaction towards loyalt customer.